Implementation of Islamic Education Values in Community Medicine Tradition in Aikmel District - Ahmad Hirsan (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study is, first, to find out the various medical traditions of the people in Aikmel. Second, gain knowledge about implementing Islamic educational values in the tradition of community medicine in the Aikmel District. This research uses qualitative methods with a qualitative descriptive approach. The study was conducted on primary data sources: treatment actors and patients. Secondary data sources are books and reference books related to the value of Islamic education, the Sasak community's medical traditions, and the ruqyah's implementation. Observation, interviews, and documentation carry out data collection techniques. Data analysis techniques using descriptive analysis. The results showed that the medical tradition of the Aikmel people was still maintained. Medical traditions include the Belian Sasak tradition, prayer water, and ruqyah. Of the three medical traditions, it is inseparable from the values of Islamic education. The values of Islamic education contained in the medical traditions of the Aikmel community include the value of aqidah/faith, tawakkal, patience, effort, worship, and moral values in the Aikmel District area. There are no medical traditions that deviate from Islamic teachings.